Uso de agua electrolizada como nueva tecnología para optimizar los procesos de limpieza y desinfección, permitiendo asegurar la calidad e inocuidad de equipos en la industria láctea. (2024)
With the purpose of contributing to the Sustainable Development Goals (SDG) and in order to design a project that generates a benefit in industrialization, innovation and infrastructure. The aim is to modernize and structure industries so that they are sustainable, using resources more effectively and promoting the adoption of clean and environmentally sound technologies and industrial processes [1]. In order to improve water quality by reducing pollution, eliminating dumping and minimizing the emission of chemicals and hazardous materials, halving the percentage of untreated wastewater and the safe reuse of water resources [2], allows research into the use of technologies that facilitate obtaining supplies for industrial cleaning and disinfection.